Boredom Susceptibility and Quit Smoking: The Role of Anxiety Symptoms. Issue 4 (19th May 2023) - Suárez-Castro, Daniel; Barroso-Hurtado, María; Martínez-Vispo, Carmela; Becoña, Elisardo; López-Durán, Ana
Abstract: Boredom is one of the main reported motives for smoking. However, scarce research has examined the relationship between boredom susceptibility and abstinence achievement in treatment-seeking smokers. The aim of this study is to examine the mediating effect of anxiety symptoms in the relationship between boredom susceptibility and abstinence at the end of a smoking cessation treatment. The sample was composed of 481 Spanish smokers who received a cognitive-behavioral treatment to quit ( M age = 45.51, SD = 11.16; 60.6% female). The Boredom Susceptibility subscale of the Sensation Seeking Scale Form-V and the Beck Anxiety Inventory were used. Pearson correlations and mediation analyses were conducted to examine the relationships between the study variables. Boredom susceptibility was significantly and positively correlated to anxiety symptoms, but not to abstinence. Anxiety symptoms were significantly and negatively correlated to abstinence. A significant indirect effect of boredom susceptibility on abstinence at the end of treatment through anxiety symptoms was found. There was no direct relation between boredom susceptibility and abstinence. These findings extend previous literature by showing that higher boredom susceptibility is associated with less likelihood to be abstinent at the end of the treatment through higher anxiety symptoms. These results highlight the relevance of considering the inclusion of boredom and anxiety management techniques in smoking cessation interventions.